Examination of Goal Commitment and Subjective Happiness Levels of the Students Studying at the Faculty of Sport Sciences According to Gender, Active Sport Participation and Sports Type Variables - Bingol, Erkan; Bingol, Duygu Yarali (Asian Journal of Education and Training, 2020)
This study was carried out to examine the goal commitment and subjective happiness levels of students studying in the faculty of sport sciences according to some variables. The research group consisted of 346 students who voluntarily participated from the faculty of sport sciences of a state university in Turkey. “Goal Commitment Scale” was used to determine the level of goal commitment of the participants, and the “Subjective Happiness Scale” was used to determine the levels of subjective happiness. Descriptive statistics were used in the analysis of demographic variables, Pearson correlation was used to determine the direction and strength of the variables, independent sample t-test was used for comparisons of the groups. The results of the study showed that subjective happiness levels of students differed according to gender and goal commitment levels differ depending on the active sport participation. In addition, significant and positive relationships were observed between the goal commitment and subjective happiness levels of the students and between the academic grade averages and the goal commitment levels. These results indicate that the goal commitment levels of students will increase as a result of encouraging active sports, and thus their academic success and subjective happiness may increase.